2012
DOI: 10.5194/acp-12-635-2012
|View full text |Cite
|
Sign up to set email alerts
|

Daytime HONO vertical gradients during SHARP 2009 in Houston, TX

Abstract: Abstract. Nitrous Acid (HONO) plays an important role in tropospheric chemistry as a precursor of the hydroxyl radical (OH), the most important oxidizing agent in the atmosphere. Nevertheless, the formation mechanisms of HONO are still not completely understood. Recent field observations found unexpectedly high daytime HONO concentrations in both urban and rural areas, which point to unrecognized, most likely photolytically enhanced HONO sources. Several gas-phase, aerosol, and ground surface chemistry mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
178
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 137 publications
(194 citation statements)
references
References 60 publications
15
178
1
Order By: Relevance
“…However, recently proposed HONO production mechanisms may be able to explain the higher levels in the East Asian megacity region. One is HONO production from NO 2 photo-excitation (Wong et al, 2012) as the region usually has high NO 2 concentrations. Zhou et al (2011) claimed that significant HONO could be generated from nitrate photolysis processes on forest canopy surface by presenting observational data from a hardwood forest in Pellston, MI.…”
Section: Observational Resultsmentioning
confidence: 99%
“…However, recently proposed HONO production mechanisms may be able to explain the higher levels in the East Asian megacity region. One is HONO production from NO 2 photo-excitation (Wong et al, 2012) as the region usually has high NO 2 concentrations. Zhou et al (2011) claimed that significant HONO could be generated from nitrate photolysis processes on forest canopy surface by presenting observational data from a hardwood forest in Pellston, MI.…”
Section: Observational Resultsmentioning
confidence: 99%
“…However, recent field observations show that daytime HONO concentrations can be substantially higher than the theoretical steady-state mixing ratio, reaching up to a few hundred ppt in urban and rural areas Acker et al, 2006a;Zhou et al, 2007;Wong et al, 2012). These elevated daytime HONO mixing ratios indicate the presence of unknown HONO formation mechanisms, which make HONO also a significant OH precursor throughout the day.…”
Section: Introductionmentioning
confidence: 98%
“…The retrieved mixing ratios were horizontally averaged between the Moody Tower and downtown Houston and vertically averaged over the LP-DOAS height intervals: lower (20-70 m), middle (70-130 m), and upper (130-300 m). Details of the experiment and data analysis are described in Wong et al (2012) and references therein. Our analysis will focus on the same sunny days as outlined in Wong et al (2012): 21 April, 17 and 18 May.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that HONO arises from the photolysis of nitric acid and nitrate or by heterogeneous photochemistry of NO 2 on organic substrates and soot (Zhou et al, 2001(Zhou et al, , 2002(Zhou et al, and 2003Villena et al, 2011;Ramazan et al, 2004;George et al, 2005;Sosedova et al, 2011;Monge et al, 2010;Han et al, 2016). Stemmler et al (2006Stemmler et al ( , 2007 found HONO formation on light-activated humic acid, and field studies showed that HONO formation correlates with aerosol surface area, NO 2 and solar radiation (Su et al, 2008;Reisinger, 2000;Costabile et al, 2010;Wong et al, 2012;Sörgel et al, 2015) and is increased during foggy periods (Notholt et al, 1992). Another proposed source of HONO is the soil, where it has been found to be co-emitted with NO by soil biological activities (Oswald et al, 2013;Su et al, 2011;Weber et al, 2015).…”
Section: Introductionmentioning
confidence: 99%